An introduction to cognitive linguistic analysis of novel name-based derivatives in the current political discourse in Poland - Góralczyk, Iwona; Paszenda, Joanna (Papers in Linguistics, 2020)
The present contribution provides a theoretical and methodological background for an analysis of novel suffixal derivatives that are based on proper names and function in the current political discourse in Poland. We delineate the most important assumptions behind a cognitive linguistic approach to word-formation, focusing particularly on one of the models within this paradigm, namely Construction Morphology. It has been demonstrated that complex words and abstract word-formation patterns can be viewed as constructions, which may be polysemous, and whose meanings may be motivated by metonymy and metaphor. It is also demonstrated that conceptual metonymy motivates the process of conversion, clipping and various types of morphological truncation. However, suffixal derivation is potentially metonymic only if the base morpheme or the suffix exhibit extended senses, or if a semantic shift applies to the derivative as a whole.